2013
DOI: 10.1186/1471-2164-14-747
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses in primary muscle cell cultures in Atlantic salmon (Salmo salar)

Abstract: BackgroundThe relationship between fish health and muscle growth is critical for continued expansion of the aquaculture industry. The effect of immune stimulation on the expression of genes related to the energy balance of fish is poorly understood. In mammals immune stimulation results in major transcriptional changes in muscle, potentially to allow a reallocation of amino acids for use in the immune response and energy homeostasis. The aim of this study was to investigate the effects of immune stimulation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 120 publications
1
33
2
Order By: Relevance
“…Interleukin-1 beta (IL-1β) is an important mediator of inflammatory response in fishes (Bo et al 2015) and innate immune mechanism (Pooley et al 2013). IL-1β as a defensive M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-1 beta (IL-1β) is an important mediator of inflammatory response in fishes (Bo et al 2015) and innate immune mechanism (Pooley et al 2013). IL-1β as a defensive M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…For example, glucocorticoids such as the cortisol-analogue dexamethasone, increase the transcription of murf1, mafbx and autophagy genes, while inhibiting protein synthesis by blocking mTor function (Braun and Marks, 2015). In addition, cytokines, such as Tnfα and IL-1β increase the transcription of E3-ubiquitin ligases, including murf1 via Nfκβ pathways (Glass, 2005;Pooley et al, 2013). Finally, fasting stimulates protein degradation by repressing Akt activation, leading to FoxO-mediated transcriptional upregulation of both E3-ubiquitin ligases and macro-autophagy genes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bonneaud et al 2003; Lochmiller and Deerenberg, 2000; Cutrera et al 2010). Recent studies in fish have revealed that the expression of certain genes from the IGF system is altered during the host defence response to bacterial and viral infections, consistent with a downregulation of growth and reallocation of resources towards immune function (Pooley et al, 2013; Alzaid et al, 2016a, 2016b). Until now, little consideration has been given to the regulation of growth pathways following immune stimulation in skeletal muscle, which is the most important target tissue for energetic investment and storage.…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-3: Foulstone et al 2003; IGFBP-5: Ren et al 2008) and inhibitory (e.g. IGFBP-2: Swiderski et al 2016; IGFBP-6: Pooley et al 2013) impacts on muscle growth. Hence, it is difficult to predict the effects that downregulation of multiple IGFBP subtypes will have in the GH transgenics, both in terms of muscle growth, but also several other metabolic phenotypes known to be regulated by this protein family (Jones and Clemmons, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation